2013
DOI: 10.1021/ma401043u
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenylenepyridyl Dendrons with Functional Periphery and Focal Points: Syntheses and Applications

Abstract: For the first time we report syntheses of a family of functional polyphenylenepyridyl dendrons with different generations and structures such as focal groups, periphery, and a combination of phenylene and pyridyl moieties in the dendron interior using a Diels−Alder approach and a divergent method. The dendron structure and composition were confirmed using NMR spectroscopy, MALDI-TOF mass spectrometry, FTIR, and elemental analysis. As a proof of concept that these dendrons can be successfully used for the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…In 2005, the synthesis of polypyridylphenylene dendrimers was reported; these dendrimers are able to capture and hold inorganic particles and, therefore, can be used for development of novel nanocomposite materials . Also, the molecular structure of polypyridylphenylene dendrimers was found to have an influence on the formation of nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the synthesis of polypyridylphenylene dendrimers was reported; these dendrimers are able to capture and hold inorganic particles and, therefore, can be used for development of novel nanocomposite materials . Also, the molecular structure of polypyridylphenylene dendrimers was found to have an influence on the formation of nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…As was discussed previously, the aggregation of the iron oxide NPs in the catalyst material via complexation with Pd NPs is crucial in order to respond to external magnetic fields. 44,45 Leaching of Catalytically Active Pd species. As is described in literature, the Suzuki coupling reaction is not taking place on the surface of Pd NPs but with palladium atoms that have been detracted from the NPs by oxidative addition to the aryl halogen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…matic dendrimers and their complexation with metals, DNA, drugs, and other compounds were investigated at length [247][248][249][250][251][252][253][254][255][256][257][258][259]. It was found that these com pounds show promise for many fields, for example, for the delivery of genes, the encapsulation of nanoparti cles by dendrimers, and the manufacture of dual action preparations.…”
Section: Dendrimersmentioning
confidence: 99%